C-type lectin receptor LSECtin-mediated apoptotic cell clearance by macrophages directs intestinal repair in experimental colitis - Yang, Zaopeng (Proc Natl Acad Sci U S A, 2018)
Epithelial barrier disruption is a major cause of inflammatory bowel disease (IBD); however, the cellular and molecular regulation of intestinal epithelial homeostasis remains largely undefined. Here, we show that the C-type lectin receptor LSECtin (Clec4g) on macrophages is required for protection against dextran sulfate sodium-induced colitis. Mechanistically, LSECtin promotes apoptotic cell clearance by macrophages and induces the production of antiinflammatory/tissue repair factors in an engulfment-dependent manner, which in turn stimulates epithelial cell proliferation. Deletion of LSECtin results in defective engulfment by colon macrophages, leading to aberrant proresolving factor production and impaired intestinal epithelium repair. Collectively, our findings suggest that LSECtin-dependent corpse clearance by macrophages can direct intestinal regeneration and maintenance of the mucosal barrier after injury.